A New Dominant Gene E9 Conditions Early Flowering and Maturity in Soybean. Issue 6 (1st November 2014) - Kong, Fanjiang; Nan, Haiyang; Cao, Dong; Li, Ying; Wu, Fangfang; Wang, Jialin; Lu, Sijia; Yuan, Xiaohui; Cober, Elroy R.; Abe, Jun; Liu, Baohui
ABSTRACT: Adaptability of soybean [ Glycine max (L.) Merr.] to a wide range of latitudes is attributed to the natural variation in the major genes and quantitative trait loci (QTL) that control flowering time and maturity. Identification of novel genes and understanding their molecular basis is critical to improving soybean productivity. We identified a new locus conditioning days to flowering and maturity that was detected in hybrid progeny between cultivated and wild soybeans. A backcross was made between the recurrent parent Tokei 780 and two early‐flowering recombinant inbred lines (RILs; from the cross Tokei 780 × Hidaka 4, a wild soybean accession, all of which possessed an identical genotype at the major four maturity loci, E1 to E4 ). The segregation patterns observed in the F2 and F3 progeny derived from the two crosses revealed that early‐flowering was controlled by a single dominant gene. The gene was fine‐mapped to a 245‐kb interval between markers M5 and M7 on Gm16. A tagging marker ID1 was significantly associated with the variation in days to flowering (0.82, p < 0.01) and maturity (0.76, p < 0.01) in the F2 population. The new early‐flowering gene and its tagging marker are very useful for molecular breeding towards early maturity and stable productivity of soybean under high‐latitude environments. The gene symbol E9e9 has been assigned. E9E9 results in early maturity and e9e9 results in late maturity.